Clinical usefulness of nocturnal urinary Noradrenaline excretion patterns in the follow-up of training processes in high-level soccer players - Naessens, G.; Chandler, J.; Kibler, W. B.; Driessens, M. (The Journal of Strength and Conditioning Research, 2000)
In order to evaluate the practical and clinical usefulness of urinary nocturnal noradrenaline excretion measurements in screening for signs of overtraining and overreaching in soccer, we studied 10 semiprofessional soccer players from a second division Belgian soccer team during their whole competitive season. We examined the relationship between their urinary nocturnal noradrenaline excretion measured both in terms of absolute (NA) and relative (NAR) values. Other variables included a modified profile of mood scoring system (POMS) as well as the time-dependent variation of those parameters. NAR values were expressed as a percentage of absolute NA values divided by the mean of those values corresponding to the lowest fatigue rate (FR) of a subject. Statistical analysis showed a cubic polynomial relationship between FR, as part of the POMS, and NA or NAR: FR = 14.90 1.91NA + 0.077NA2 0.00092NA3; FR = 12.22 0.25NAR + 0.0016NAR2 0.0000030NAR3. Grouping the NAR values (group 1 < 60%, 60% group 2 140%, and group 3 > 140%), analyzed over different time periods, showed varying degrees of significant differences for each period in FR between the three groups. Assuming that a prolonged increment of FR is a major sign of training maladaptation and performance decrement and since there were also two players with an apparent overtraining syndrome (lowest NAR values) during the observation period, the following hypotheses are suggested: (a) Overreaching can be characterized by an increase or decrease in NAR of more then 40%, while overtraining is suggested by decreases of more than 60%. (b) The winter break period reduces the number of overreached or overtrained subjects. (c) Preseason conditioning is not always optimal, indicating a need for partial individualization of the training programs. (d) Nocturnal urinary noradrenaline excretion measurements can be used as a valuable tool in monitoring overreaching and overtraining in high-level soccer players.